Determination of mall building vertical displacements by sedimentary marks - Serant, Oksana; Sidorov, Ihor; Balyan, Andrij; Kubrak, Olena; Yarema, Nataliya; Dzhuman, Bohdan (Geodesy and Cartography, 2022)
The purpose of this paper is to determine the optimal method of researching the vertical displacements of buildings and stability of the marks, on the basis of which it is possible to make a conclusion about the subsidence of the researched building. Methodology. The main task of geodetic observations for buildings monitoring is to identify changes in the spatial position of load-bearing structures (vertical and horizontal displacements) to assess the risk of structures destruction, dismantling unstable structures, forecasting accidents. In this paper we offered to carry out monitoring by a method of high – precision geometrical leveling on the established geodetic marks, according to one scheme with constant points of devices installation. For testing this method 13 cycles of II class leveling were conducted to determine the vertical displacements of sedimentary marks of the “Shuvar” mall building. To detailed determination of the building deformation, namely its sediment on two floors, we laid 70 marks in the floor on the first floor and 41 marks on the second floor. Stainless steel anchors were used as marks. Findings. According to the results of observations of the laid sedimentary marks we determined their conditional heights. The difference of determined heights of the same marks for a certain period of time allows to determine the vertical displacements. The results of measurements were equilibrated by the nodal point method, and the leveling line was closed on each floor, so the equilibrations were performed separately for each floor. As a result we obtained the heights of sedimentary marks and the mean square errors of their determination. We constructed schedule of heights change of the chosen marks of the first floor within 13 cycles andcarried out the analysis of the reasons of these changes. Practical implications and originality. Observations of landslides, subsidences and deformations of the building have great importance for determining the strength and stability of the building to prevent its destruction or give signal in a timely manner of an emergency, which can become vital. In this paper method for monitoring the vertical displacements of buildings is proposed and tested. The obtained results suggest that proposed method of observations can be recommended to determine the vertical displacements of such buildings and complexes.